Reconstructing Education Management in the Post-Pandemic Technology Era - Ali Rohmad (JIE (Journal of Islamic Education), 2023)
The purpose of this research is to find out the ability of students to view and examine less material education. This research uses the qualitative library resource method to examine libraries using secondary data collection. Secondary data is data from scientific writings, books, and news that are linear with this research. The results of this study reveal a reformulation of the concept of education amid today's technological development. Reform is an educational institution that collaborates with organisations to know the human potential to create a professional and qualified SDM. Within such organisations are changemakers hubs, which enable individuals to make a change or innovation movement. Thus, civilisations are also ready for technological advances.